Heterologous prime-boost: breaking the protective immune response bottleneck of COVID-19 vaccine candidates - He, Qian; Mao, Qunying; An, Chaoqiang; Zhang, Jialu; Gao, Fan; Bian, Lianlian; Li, Changgui; Liang, Zhenglun; Xu, Miao; Wang, Junzhi (Emerging microbes & infections, 2021)
COVID-19 vaccines emerging from different platforms differ in efficacy, duration of protection, and side effects. To maximize the benefits of vaccination, we explored the utility of employing a heterologous prime-boost strategy in which different combinations of the four types of leading COVID-19 vaccine candidates that are undergoing clinical trials in China were tested in a mouse model. Our results showed that sequential immunization with adenovirus vectored vaccine followed by inactivated/recombinant subunit/mRNA vaccine administration specifically increased levels of neutralizing antibodies and promoted the modulation of antibody responses to predominantly neutralizing antibodies. Moreover, a heterologous prime-boost regimen with an adenovirus vector vaccine also improved Th1-biased T cell responses. Our results provide new ideas for the development and application of COVID-19 vaccines to control the SARS-CoV-2 pandemic.